Characteristics of Digital And Manual Archive Management - Triana, Apri; Halimi, Halimi; Hidayatullah, Syarif; Iqbal, Zikri Muhammad (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This research aims to exploratively describe the characteristics of archive management at UIN SMH Banten. The characteristics referred to are the percentage of manual or digital archive management. There is also an explanation of the many static and dynamic archives managed at UIN SMH Banten. Apart from the percentages at the archive management stage, several obstacles faced by archivists in managing archives at UIN SMH Banten were also discussed. To obtain valid and credible data, questionnaires, interviews and documentation were used. The informants in this research were all archivists who were tasked with managing archives at UIN SMH Banten. From the results of data collection and analysis, it was found that archive management is generally carried out manually and digitally. Even though archives have been managed manually and digitally, archive management is still dominated by manual methods. The archives that are mostly managed by archivists at UIN SMH Banten are dynamic archives. Digitally managed archives are not yet fully integrated at the university level. Meanwhile, archives that are managed manually are still not in accordance with the archive management classification. One of the obstacles to archival management at UIN SMH Banten is the lack of archival facilities and infrastructure which results in problems with digital archive integration.